The Limited Role of the Japanese Military: The 2003 Iraq War and the War on the Islamic State - Boduszyński, Mieczysław P.; Lamont, Christopher K.; Streich, Philip (WILAYAH: The International Journal of East Asian Studies, 2021)
What determines Japan’s willingness to flex its limited military muscle abroad? While analysts and scholars closely watched Japanese "militarization" under Prime Minister Shinzo Abe (2012-2020), Japan had already deployed its military overseas over a decade ago in support of U.S. operations in Iraq and Afghanistan. By contrast, in 2014, Japan was unwilling to support U.S.-led operations against the Islamic State (ISIL) in Iraq and Syria. This presents a puzzle, as the fight against ISIL offered the kind of international legitimacy that the 2003 Iraq invasion lacked, and Japan traditionally seeks. Moreover, ISIL had killed Japanese citizens. This paper explains Japan’s varying policies in Iraq in 2003 and 2014, thereby shedding light on the determinants of Japanese national security policy more generally. Our argument focuses on domestic political factors (especially the pluralist foreign policymaking) and strategic thinking rooted in realism. We argue that Japanese policies are driven by domestic politics, profound suspicions about the utility of military force and fears of becoming entangled in a seemingly never-ending conflict. While Koizumi may have had more room to manoeuvre despite long-standing public opposition to overseas military deployments when he dispatched the SDF to Iraq in 2003, it is precisely such deeply-entrenched popular anathema that many blame for the Liberal Democratic Party’s (LDP) historic and devastating loss in the 2009 election. Abe was unwilling to repeat such a risky venture in 2014. We also highlight the role of realist calculations on both Japanese elites and the public, who by 2014 had come to see China rather than state or non-state actors in the Middle East as a primary security threat. We thus confirm Midford’s finding that "defensive realism" tends to drive Japanese foreign policy thinking. Japanese citizens are not pacifists, as conventional wisdom might hold. Instead, Japanese public opinion supports the use of minimum military force when and if Japan is attacked to defend Japan’s national sovereignty and territory but is much more suspicious of such power when it comes to deployments and the pursuit of other foreign policy goals.